A Comprehensive Ayurvedic Approach to Multisystem Disease (AYUSHDHARA, 2025)
Chronic liver disease is a progressive condition that may result from multiple etiologies including alcohol abuse, recurrent jaundice and metabolic disorders. Management is challenging in patients with multiple co-morbidities. Decompensated liver disease also knows as de-compensated cirrhosis when the liver damaged can no longer compensate for its impaired functions. This stage signifies a severe decline in liver functions and can be life threatening if not addressed often requires liver transplant. As a complication it leads to serious complications like hepatorenal syndrome. Conventional medicine primarily focuses on disease specific pharmacological control there by limiting the scope for holistic recovery. This case repost presents a 55yr old male parent with a complex history of decompensated liver disease chronic kidney disease, type 2 diabetes mellites, hypertension and cardio vascular disease, cerebro vascular accident. An integrated approach using classical Ayurvedic management and panchakarma procedures was adopted over 12 months of outpatient treatment, the patient showed marked improvement is liver function, glycemic control, renal markers and blood pressure regulations without hospitalization. This case highlights the potentials of Ayurvedic intervention is Chronic multi system condition where standard treatment plateau. In Ayurveda, CKD can be correlated with various forms of Mootraghata, a Tridoshaja condition where urine formation is impaired due to intrinsic and extrinsic factors such as suppression of natural urges, intake of Ruksha Padartha, Tikshna Aushadha, and obesity-related Medovaha Srotodushti. The pathology primarily involves Vata Prakopa in the Basti region. Considering the similarity in symptoms, Ayurvedic management of CKD emphasizes Sthoulyahara (anti-obesity), Mootrala, and Mootraghatahara approaches along with Shotha Vyadhi Chikitsa. This case study illustrates a safe and effective Ayurvedic alternative for CKD management.